2019
DOI: 10.4018/978-1-5225-8461-2.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of Indicators for Intellectual Capital in Higher Education

Abstract: The objective of the chapter is to provide a proposal of indicators of intellectual capital in higher education for the organizations that comprise it. The importance of valuing intellectual capital in educational organizations is to measure their contributions to society, which complement the financial landscape and allow comparison between similar institutions, in order to compare their performance. Therefore, the conclusion of carrying out this process in higher education is 1) providing adequate informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…, 2020). Several researchers (Edvinsson and Malone, 1997; Rodrigues and Dorrego, 2008) emphasised that structural capital represents the real ability of the organisation to, in the process of transporting and storing intellectual materials, protect them from loss and damage over time and improve the knowledge infrastructure of the organisation (De Pablos, 2004; Espinosa, 2019; Pandey and Dutta, 2013). Organisational success can be achieved by using these processes and procedures to develop innovative organisational activities that can help the organisation achieve a competitive advantage (Hejazi et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2020). Several researchers (Edvinsson and Malone, 1997; Rodrigues and Dorrego, 2008) emphasised that structural capital represents the real ability of the organisation to, in the process of transporting and storing intellectual materials, protect them from loss and damage over time and improve the knowledge infrastructure of the organisation (De Pablos, 2004; Espinosa, 2019; Pandey and Dutta, 2013). Organisational success can be achieved by using these processes and procedures to develop innovative organisational activities that can help the organisation achieve a competitive advantage (Hejazi et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The importance and role of relational capital and innovation performance have been widely discussed in the literature (Sardo and Serrasqueiro, 2017). Relational capital includes a set of social, institutional and economic relationships and networks that the organisation forms through its interaction with stakeholders in their various activities (Espinosa, 2019; Saad and Jedin, 2016). Relational capital can be represented by the added value of the social relations inside and outside the organisation (Lenart-Gansiniec, 2016).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…AlQershi et al. (2020), Espinosa (2019) and Valeri and Katsoni (2021) confirmed that companies' strategic use of their formal and informal social relationships improves the exchange of knowledge between the external environment and the company as well as of experiences and knowledge amongst individuals within the company (Buenechea-Elberdin et al. , 2018a, b; Ryu et al.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 96%
“…They confirmed SC provides the ability to achieve sustainable CAs by transferring and storing knowledge and sharing that knowledge within the company. This helps the company retain knowledge and thus improve operations and activities as well as organisational performance by directing these capabilities towards innovation (Espinosa, 2019; Hejazi et al. , 2016).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation